Management of a Critical Case of Double Outlet Right Ventricle (DORV) and Cerebral Abscess by Multiple Interventions - Begum, Nurun Nahar Fatema; Sarker, Ferdousur Rahman; Begum, Maksuda; Yesmin, Tamanna; Hossain, Billal; Ferdous, Jannatul; Hossain, Jahangir; Salek, Md Al Amin (Journal of Armed Forces Medical College, Bangladesh, 2016)
Tetralogy of Fallot (TOF) is the commonest type of cyanotic congenital heart disease which accounts for 10% of all congenital heart disease. Delay in surgical treatment leads to polycythaemia, cerebral abscess, thrombotic episodes etc. Corrective surgery in a case with cerebral abscess always has risk of intracranial hemorrhage during bypass1. We are hereby reporting a case of TOF who had multiple cerebral abscess managed with burr hole operation and extra ventricular drainage. Later 5 coronary stents were placed in Right Ventricular Outflow Tract (RVOT) to Main Pulmonary Artery (MPA) to overcome infundibular and valvular stenosis and thus reducing right to left shunt and cyanosis. This is the first ever palliation with RVOT stenting in a case of Double Outlet Right Ventricle (DORV), Ventricular Septal Defect (VSD), Pulmonary Stenosis (PS) with cerebral abscess where surgery was contraindicated at that time and patient condition was unstable. Later on she had bidirectional Glenn shunt on 8th December 2015 by Saudi charity team. Journal of Armed Forces Medical College Bangladesh Vol.11(1) 2015: 81-84